SARS-CoV-2 infection in China-Before the pandemic. - Huiying Liang; Lingling Zheng; Huimin Xia; Jinling Tang (Public Library of Science (PLoS), 2020)
In order to rapidly inform polices in the international response to the ongoing pandemic of coronavirus disease 19 (COVID-19), we summarize in this review current evidence on epidemiological and clinical features of the infection, transmission routes, problems of nucleic-acid testing, the epidemiological trend in China and impact of interventional measures, and some lessons learned. We concluded that the epidemic is containable with traditional nonpharmacological interventions, mainly through social distancing and finding and isolating suspected patients and close contacts. Nonpharmacological interventions are the only effective measures currently accessible and have suppressed some 90% of the infections in China. Close contacts are the major mechanism of transmission, which makes it possible to control this epidemic through nonpharmacological methods. Nucleic-acid testing alone may miss some 50% of infected patients, and other methods such as chest computerized tomography (CT) or serology should be considered to supplement molecular testing. The development of vaccines and drugs is important, but hesitation to make use of nonpharmacological interventions may mean missing golden opportunities for effective actions.